Effects of ammonium sulphate hardener and amine compound on formaldehyde emission of particleboard bonded at varies levels of urea formaldehdye resin - Wahab, Mohammad Waridwan (2017)
Particleboard is an engineered wood that is manufactured from wood chips and synthetic resin or other suitable binder which is pressed. It is also known as a structural material that was made from wood particles, such as chips, shavings or even sawdust that are mechanically pressed into sheet form and bonded with or without resin. However, the uses of urea formaldehyde (UF) in the manufacturing of particleboard possess great disadvantage such as emission of formaldehyde which are irritation in the upper respiratory tract and combustion in the eyes. Several methods have been successfully developed in the reduction of formaldehyde emission (FE). One of the method that has been used is modifying the chemistry of UF resin by using hardener. The main objective of this study is to study the effects of ammonium sulphate and amine compound as hardener on formaldehyde emission of particleboard bonded of varies concentration of UF resin. In this study, raw materials consisting of rubberwood and five different concentration of Urea formaldehyde (UF) were applied to manufactured particleboard, which were 10%, 12% 14% and 16%. The temperature applied was 180oC and pressing time was 4 minutes. The result showed that the formaldehyde emission increase as the concentration increase. The study was also found that density was increasing and the moisture content (MC) was decreasing along the increasing of concentration. The treatment was also found to increase the dimensional stability and mechanical properties of the particleboard. As regards with urea formaldehyde (UF) concentration, there was no significant different in mechanical properties but differ significantly in physical properties.